Research on health equity in the SDG era: the urgent need for greater focus on implementation - Rasanathan, Kumanan (Int J Equity Health, 2016)
BACKGROUND: The tremendous increase in knowledge on inequities in health and their drivers in recent decades has not been matched by improvements in health inequities themselves, or by systematic evidence of what works to reduce health inequities. Within health equity research there is a skew towards diagnostic studies in comparison to intervention studies showing evidence of how interventions can reduce disparities. MAIN TEXT: The lack of sufficient specific evidence on how to implement specific policies and interventions in specific contexts to reduce health inequities creates policy confusion and partly explains the lack of progress on health inequities. In the field of research on equity in health, the time has come to stop focusing so much energy on prevalence and pathways, and instead shift to proposing and testing solutions. Four promising approaches to do so are implementation research, natural experimental policy studies, research on buy-in by policy-makers to action on health inequities, and geospatial analysis. CONCLUSION: The case for action on social determinants and health inequities has well and truly been made. The community of researchers on health equity now need to turn their attention to supporting implementation efforts towards achievements of the Sustainable Development Goals and substantive reductions in health inequities.